2020
DOI: 10.1590/s1808-185120201902224026
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Analysis of the Results of Anterior Internody Arthrodesis on the Sagittal Lumbopelvic Parameters

Abstract: Objective The objective of this study is to analyze the radiographs of patients who underwent anterior lumbar interbody fusion (ALIF), to compare the values of the lumbopelvic measurements, and to quantify improvements in these parameters achieved through this technique. Methods The radiographs of 42 patients, all submitted to ALIF with a 12° interbody device, were evaluated from a database at a single center. The pelvic incidence, pelvic tilt, sacral slope, lumbar lordosis, segmental lordosis, and regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(10 reference statements)
0
0
0
1
Order By: Relevance
“…This author believes that the antalgic kyphotization may have influenced these values in the radiograph caused by pain in the immediate postoperative period (PO), considering that the control radiographs were performed in the early PO. 17 In our study, an increase in lumbar lordosis and the anterior and posterior height of the intervertebral disc was observed after ALIF…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This author believes that the antalgic kyphotization may have influenced these values in the radiograph caused by pain in the immediate postoperative period (PO), considering that the control radiographs were performed in the early PO. 17 In our study, an increase in lumbar lordosis and the anterior and posterior height of the intervertebral disc was observed after ALIF…”
Section: Discussionsupporting
confidence: 52%
“…1 No patient in this study had postoperative neurological damage with indirect decompression, corroborating previously published papers in the literature. 1 Nanni FN et al, 17 in their study on radiographic evaluation of patients undergoing ALIF -observed increased segmental lordosis and reduced lumbar lordosis. This author believes that the antalgic kyphotization may have influenced these values in the radiograph caused by pain in the immediate postoperative period (PO), considering that the control radiographs were performed in the early PO.…”
Section: Discussionmentioning
confidence: 95%
“…Portanto, reforçar-se a necessidade de ampliar esta pesquisa em uma amostra maior. Ademais, enfatiza-se que deve ser futuramente analisado em outros estudos: estratégias de prevenção e recuperação da saúde postural entre estudantes do ensino superior, formas de tratamento, desenvolvimento de dispositivos de prevenção e avaliação postural e investigar a relação entre variáveis como tempo de estudo, área profissional de atuação e alterações posturais escolióticas [21][22][23].…”
Section: Discussionunclassified